2016
DOI: 10.1001/jamadermatol.2016.0502
|View full text |Cite
|
Sign up to set email alerts
|

Bundled Payment Models for Actinic Keratosis Management

Abstract: IMPORTANCE Recent legislation encourages alternative payment models, such as bundled payments. There are no clear recommendations on bundled payment design, and research on bundled payments for dermatologic care is limited. OBJECTIVE To investigate several methods to develop bundled payment models for actinic keratosis (AK) management and the likely effect on the cost of AK management. DESIGN, SETTING, AND PARTICIPANTS Cohort cost identification study using claims from Highmark Insurance and the MarketScan Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Thirteen articles in this review reported reductions in health expenditures associated with bundled payment reforms [19, 27, 34–44]. Four articles reported no or unclear effects of bundled payments on system-wide costs savings [41, 4547].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles in this review reported reductions in health expenditures associated with bundled payment reforms [19, 27, 34–44]. Four articles reported no or unclear effects of bundled payments on system-wide costs savings [41, 4547].…”
Section: Resultsmentioning
confidence: 99%
“…One article indirectly touched on equity concerns in the context of bundled payment for the management of solar keratosis, a precancerous skin lesion [41]. Study findings suggested that those not covered by the coverage scheme employing this payment model will have differential access to services and that this access will depend on design elements of the payment mix reforms, particularly the capacity of a purchaser to appropriately adjust for risk.…”
Section: Resultsmentioning
confidence: 99%
“…With changing payment models and the potential for bundled reimbursement for clearance of AK, knowledge of which therapies achieve and sustain the highest degree of clearance may have financial implications in the future. 7 Limitations of the study include the small sample size and the single clinical setting, in addition to the fact that our observations spawned from a QI project. Moreover, only actinic keratoses were studied, and the selfreported nature of the primary outcomes is subject to recall bias.…”
Section: Resultsmentioning
confidence: 99%
“…Although alternative payment methods are currently being used and developed throughout the US, such as bundled payment models for actinic keratosis management, working in a value-based manner remains relatively novel in the field of dermatology. 15,16 Determining which outcomes to measure is an important first step in the transition to a value-based approach. There are, however, several considerations that need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%